Renal function following liver transplantation for unresectable hepatoblastoma - Lee, W.S.; Grundy, R.; Milford, D.V.; Taylor, C.M.; de Goyet, J.D.; McKiernan, P.J.; Beath, S.V.; Kelly, D.A. (2003)
Combination of cyclosporine (CsA) and tacrolimus immunosuppression post-liver transplantation (LT) and the chemotherapeutic drugs used to treat hepatoblastoma (HB), are nephrotoxic. We aimed to determine the severity and duration of nephrotoxicity in children following LT for unresectable HB. We reviewed all children undergoing LT for unresectable HB at the Liver Unit, Birmingham Children's Hospital, UK, from 1991 to July 2000. Thirty-six children undergoing LT for biliary atresia, matched for age and sex, were selected as controls to compare pre- and post-LT renal function. Renal function was determined by estimation of glomerular filtration rate (eGFR) derived from plasma creatinine using Schwartz's formula. Twelve children with HB (mean age of diagnosis 33 months) who underwent LT (mean age 47 months) and 36 controls (mean age of LT 34 months) were studied. CsA was the main immunosuppressive drug used in each group. The median eGFR before, and at 3, 6, 12, 24 and 36 months after LT in HB group was significantly lower than controls (93 vs. 152, 66 vs. 79, 62 vs. 86, 66 vs. 87, 64 vs. 94, 53 vs. 90 mL/min/1.73 m(2) , respectively; 0.01 < p < 0.03). The reductions in the median eGFR of both the HB group and controls before and at 36 months after LT were 49 and 41, respectively. At 36 months after LT, there was a trend for partial recovery of the eGFR in the controls but not in the HB group. Children who underwent LT for unresectable HB had renal dysfunction before transplantation that persisted for 36 months after LT.